Redox state and metabolic responses to severe heat stress in lenok Brachymystax lenok (Salmonidae) - Yan Chen; Zhe Pan; Yucen Bai; Shaogang Xu (Frontiers in Molecular Biosciences, 2023)
In order to provide new insights into the physiological responses of lenok (Brachymystax lenok: Salmonidae) to acute and severe heat stress (25°C, 48 h), dynamic changes in redox state and metabolic responses are studied combined biochemical index and non-targeted metabolome. Nicotinamide adenine dinucleotide (NAD+) consumption causes significant increases in ratio of reduced NADH to NAD+ and ratio of reduced nicotinamide adenine dinucleotide phosphate (NADPH) to NADP+, which induced the redox imbalance in heat stressed lenok. Lowered reduced glutathione/oxidized glutathione (GSH/GSSG) ratios suggested that more oxidized conditions occurred in heat-stressed lenok, leading to membrane lipid oxidation. The first few hours of heat stress promoted the activity of enzymes involved in anaerobic glycolysis (hexokinase, pyruvate kinase, lactic dehydrogenase) and glutamicpyruvic transaminase and glutamic oxaloacetic transaminase, which might lead to consumption of many carbohydrates and amino acid catabolism. These enzyme activities decreased with time in a possible compensatory strategy to manage anabolic and catabolic metabolism, maintaining the redox homeostasis. After 48 h of recovery, NAD+, carbohydrate levels and enzyme activities had returned to control levels, whereas many amino acids were consumed for repair and new synthesis. GSH remained at levels lower than controls, and the more oxidized conditions had not recovered, aggravating oxidative damage. Glutamic acid, glutamine, lysine and arginine may play important roles in survival of heat-stressed lenok.